1965
DOI: 10.1126/science.150.3697.763
|View full text |Cite
|
Sign up to set email alerts
|

Cestode in North Dakota: Echinococcus in Field Mice

Abstract: Field mice (Microtus pennsylvanicus and Peromyscus maniculatus) are naturally infected with Echinococcus multilocularis. Thus, the sylvatic cycle (fox to field mice to fox) has been established in North Dakota. This cestode is expected to extend its range to other agricultural regions of the continental United States where similar conditions favorable for the completion of its life cycle exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The purpose of this paper is to summarize these findings, with remarks on their epidemiological significance. Some of the data presented herein have been reported in previous papers (Leiby, 1965;Carney and Leiby, 1968). These papers and other reports on the sylvatic occurrence of E. multilocularis in the conterminous United States and southern Canada are summarized in Table I.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The purpose of this paper is to summarize these findings, with remarks on their epidemiological significance. Some of the data presented herein have been reported in previous papers (Leiby, 1965;Carney and Leiby, 1968). These papers and other reports on the sylvatic occurrence of E. multilocularis in the conterminous United States and southern Canada are summarized in Table I.…”
mentioning
confidence: 70%
“…The specimens were fixed in 10% formalin and stained with Mayer's carmalum. Microtus pennsylvanicus Ord North Dakota Leiby (1965) Saskatoon, Saskatchewan Hnatiuk (1966) Peromyscus maniculatus (Wagner) North Dakota Leiby (1965) Minnesota Carney and Leiby (1968) Winnipeg, Manitoba Leiby et al (1969) Lee (1969 Vulpes vulpes L. North Dakota Leiby and Olsen (1964) Richards (1966) Rausch (1967) Saskatoon, Saskatchewan Hnatiuk (1969) Minnesota Camey and Leiby (1968) * Rausch (1967) concluded that the report by Magath (1965) of E. multilocularis cysts from the liver of a beef cow in Iowa was based upon the multivesicular form of E. granulosus.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The larval stage has been found in the meadow vole, Microtus pennsylvanicus Ord, and in the white-footed mouse, Peromyscus maniculatus (Wagner), by Leiby (1965) and by S. H. Richards, North Dakota Game and Fish Department, Bismarck (unpublished data). Findings in a large series of red foxes examined by Rausch and Richards indicate that the Cestode is widely established in North Dakota.…”
Section: Infection In Man Was First Recognized In 1937 Approximatelymentioning
confidence: 92%
“…The life cycle of E. mU/liiocu/aris in central North America involves the red fox and coyotes as final hosts; up to 70 percent of red foxes in North Dakota were found to be infected (Leiby andOlsen 1964, Leiby 1965). …”
mentioning
confidence: 99%